Extracellular Calmodulin-Induced Stomatal Closure Is Mediated by Heterotrimeric G Protein and H(2)O(2) - Chen, Yu-Ling (American Society of Plant Biologists, 2004)
Extracellular calmodulin (ExtCaM) exerts multiple functions in animals and plants, but the mode of ExtCaM action is not well understood. In this paper, we provide evidence that ExtCaM stimulates a cascade of intracellular signaling events to regulate stomatal movement. Analysis of the changes of cytosolic free Ca(2+) ([Ca(2+)](cyt)) and H(2)O(2) in Vicia faba guard cells combined with epidermal strip bioassay suggests that ExtCaM induces an increase in both H(2)O(2) levels and [Ca(2+)](cyt), leading to a reduction in stomatal aperture. Pharmacological studies implicate heterotrimeric G protein in transmitting the ExtCaM signal, acting upstream of [Ca(2+)](cyt) elevation, and generating H(2)O(2) in guard cell responses. To further test the role of heterotrimeric G protein in ExtCaM signaling in stomatal closure, we checked guard cell responses in the Arabidopsis (Arabidopsis thaliana) Gα-subunit-null gpa1 mutants and cGα overexpression lines. We found that gpa1 mutants were insensitive to ExtCaM stimulation of stomatal closure, whereas cGα overexpression enhanced the guard cell response to ExtCaM. Furthermore, gpa1 mutants are impaired in ExtCaM induction of H(2)O(2) generation in guard cells. Taken together, our results strongly suggest that ExtCaM activates an intracellular signaling pathway involving activation of a heterotrimeric G protein, H(2)O(2) generation, and changes in [Ca(2+)](cyt) in the regulation of stomatal movements.